Production of embryos of an endangered species (Bos gaurus) by the xenogenic nuclear transfer into the ooplast of the domestic cow for preservation of this animal in VietNam - Ty, Le Van; Son, Hoang Nghia; Hanh, Nguyen Van; Duc, Nguyen Huu; Nguyen, Bui Xuan (Academia Journal of Biology, 2015)
Advanced reproductive technologies, including in vitro fertilization, nuclear transfer and embryo transfer are becoming increasingly important for the preservation of endangered animal species. The goal of this investigation is to preserve the somatic cell of the unique bull of Bos gaurus captured in Vietnam (Zoo park of Hochiminh city) and to use this cell as nuclear donor, transferred into xenogenic ooplasts from matured oocytes of domestic cattle (Bos indicus). The Bos gaurus ear fibroblast cell culture, freezing and thawing until the 19th passage shown their typotency to develop in vitro: the characteristic behaviour of multiplication, the stability of number and morphology of chromosomes, the capability to be activated by ooplast and developed into blastocyt. The comparison of reconstructed embryos of Bos gaurus and Bos indicus cells with the ooplast from the later presented the similarity for all steps the development: the rate of cleavage was from 41-60%, the percentage of the embryos developed into blastocytes was approximately 10% of used oocytes, the hatching was observed in both case at 9th day. In conclusion, the techniques of culture and freezing were satisfied for the cryoconservation of tissues and cells of endangered wild animals and ooplasts from matured oocyte of domestic cattle could not only harbor the progeny of Bos gaurus, but activate the nuclei of its cell to produce embryos until blastocyst.